2020
DOI: 10.11606/s1518-8787.2020054001704
|View full text |Cite
|
Sign up to set email alerts
|

Food processing and cardiometabolic risk factors: a systematic review

Abstract: OBJECTIVE: To systematically review the evidence for the association between food consumption according to processing and cardiometabolic factors in adults and/or the elderly. METHOD: Two independent evaluators analyzed the electronic databases PubMed, Web of Science and Lilacs until December 2018. We used the following terms: (convenience foods OR food processing OR highly-processed OR industrialized foods OR minimally-processed OR prepared foods OR processed foods OR ultra-processed OR ultraprocessed OR ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 43 publications
0
36
0
10
Order By: Relevance
“…Os achados deste estudo, somados aos de estudo similar sobre a versão do escore utilizada pelo sistema Vigitel 14 , indicam ser possível monitorar a participação de alimentos ultraprocessados na dieta de forma eficaz, rápida e prática. Note-se que essa participação vem sendo associada, no Brasil e em vários países do mundo, à intensa deterioração da qualidade das dietas 3 e ao risco aumentado de obesidade, diabetes, doenças cardiovasculares e várias outras doenças crônicas não transmissíveis de grande relevância epidemiológica [4][5][6][7][8][9][10] . Como parte do programa Immana (The Innovative Methods and Metrics for Agriculture and Nutrition Actions), baseado na London School of Hygiene and Tropical Medicine c , o rastreador Nova de consumo de alimentos ultraprocessados está sendo adaptado para uso na Índia, Senegal e Equador, o que permitirá que o desempenho do escore Nova de consumo de alimentos ultraprocessados seja estudado em outros países.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os achados deste estudo, somados aos de estudo similar sobre a versão do escore utilizada pelo sistema Vigitel 14 , indicam ser possível monitorar a participação de alimentos ultraprocessados na dieta de forma eficaz, rápida e prática. Note-se que essa participação vem sendo associada, no Brasil e em vários países do mundo, à intensa deterioração da qualidade das dietas 3 e ao risco aumentado de obesidade, diabetes, doenças cardiovasculares e várias outras doenças crônicas não transmissíveis de grande relevância epidemiológica [4][5][6][7][8][9][10] . Como parte do programa Immana (The Innovative Methods and Metrics for Agriculture and Nutrition Actions), baseado na London School of Hygiene and Tropical Medicine c , o rastreador Nova de consumo de alimentos ultraprocessados está sendo adaptado para uso na Índia, Senegal e Equador, o que permitirá que o desempenho do escore Nova de consumo de alimentos ultraprocessados seja estudado em outros países.…”
Section: Discussionunclassified
“…Inquéritos nutricionais realizados em amostras probabilísticas da população de vários países evidenciam que o consumo de alimentos ultraprocessados, medido pelo percentual da ingestão total de energia relativa a esses alimentos, está forte e inversamente relacionado à qualidade nutricional da dieta 3 . Revisões sistemáticas de estudos de coorte bem conduzidos e de grande porte mostram que o mesmo percentual calórico proveniente de alimentos ultraprocessados está diretamente associado ao risco de doenças crônicas não transmissíveis, como obesidade, diabetes, hipertensão, dislipidemias, doenças cardio e cerebrovasculares, câncer em geral, câncer de mama e depressão, assim como à mortalidade precoce por qualquer causa [4][5][6][7][8][9][10] .…”
Section: Introductionunclassified
“…By contrast, UPF consumption has previously been associated with hypertension, diabetes, obesity and metabolic syndrome [ 45 ], which in turn, are major risk factors for renal function impairment. In addition, in our study UPF consumption increased the risk of renal function decline independently of hypertension, diabetes, BMI, as well as other chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a higher consumption of foods in this processing level was still associated with a nutritionally inadequate diet (i.e., higher energy and carbohydrate intake and lower protein intake), which is in line with other studies that also reported an association between ultraprocessed food consumption and less desirable dietary patterns ( 34 36 ). Particular attention should be given to high consumers of ultraprocessed foods during the COVID-19 pandemic, as this type of food is associated with increased adiposity ( 37 40 ), even in a short period of time ( 41 ).…”
Section: Discussionmentioning
confidence: 99%